2002
DOI: 10.1128/jvi.76.18.9152-9164.2002
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Human Immunodeficiency Virus Type 1 Expression by Caveolin-1

Abstract: Caveolin-1 (Cav-1) is a major protein constituent of caveolae, a type of plasma membrane raft. We observed that coexpression of human Cav-1 with human immunodeficiency virus type 1 (HIV-1) blocked virion production from cells that are ordinarily highly permissive. Further investigation showed that this effect is specific, occurs at low ratios of Cav-1 to HIV-1 DNA, depends on expression of Cav-1 protein, and involves severely impaired expression of HIV-1 proteins. Cav-1 also blocked HIV-2 expression. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…The strong association of Cav-1 with the HIV Env, which is mediated by the gp41 region, suggests a role for Cav-1 in HIV infection and pathogenesis. In support of this, inhibition of virus production is observed in fibroblast cells transfected with HIV provirus DNA in cells where Cav-1 is overexpressing (31). Furthermore, we recently reported Cav-1 can block HIV Env-induced apoptosis of innocent bystander cells as well as inhibition of Envmediated effector/target cell fusion, implicating the role of Cav-1 in inhibiting virus production by interaction with Env (47).…”
mentioning
confidence: 86%
“…The strong association of Cav-1 with the HIV Env, which is mediated by the gp41 region, suggests a role for Cav-1 in HIV infection and pathogenesis. In support of this, inhibition of virus production is observed in fibroblast cells transfected with HIV provirus DNA in cells where Cav-1 is overexpressing (31). Furthermore, we recently reported Cav-1 can block HIV Env-induced apoptosis of innocent bystander cells as well as inhibition of Envmediated effector/target cell fusion, implicating the role of Cav-1 in inhibiting virus production by interaction with Env (47).…”
mentioning
confidence: 86%
“…We have also shown that HIV infection in primary human monocyte-derived macrophages (MDMs) results in a dramatic upregulation of Cav-1 expression mediated by HIV Tat (31). The overexpression of Cav-1 significantly inhibits HIV replication (31,34), implicating Cav-1 as playing a role in HIV's persistent infection of macrophages. However, the mechanism by which Cav-1 inhibits HIV replication remains to be determined.…”
mentioning
confidence: 87%
“…We and others have previously reported that Cav-1 inhibits HIV replication (31,34). In order to determine the mechanisms of Cav-1-mediated reduction of HIV replication, we evaluated the expression of luciferase under the control of the HIV LTR using a provirus that is defective for Env and has the coding sequence of luciferase placed in the Nef region (pNL4-3.Luc.R Ϫ E Ϫ ).…”
Section: Cav-1 Inhibits Gene Expression Under the Control Of The Hiv mentioning
confidence: 99%
“…Primers for HIV-1 were 5Ј-ATATTCTAGAATGTTTTTAGATGGAATAGATAAGGCCC-3Ј and 5Ј-ATATGGGCCCATCCTCATCCTGTCTACCTGCC-3Ј. The amplicons were inserted as Xba/ApaI fragments into pCMV-Myc, which contains the promoter and intron A of the human cytomegalovirus (CMV) immediate early gene (45). MoMLV integrase was amplified with 5Ј-ATATGAATTCATGATAGAA AATTCATCACC-3Ј and 5Ј-TATAGAATTCTTACAGATCCTCTTCTGAGA TGAGTTTTTGTTCGGGGGCCTCGCGG-3Ј and inserted as EcoRI fragments into pCMV and pCMV2, which lacks intron A.…”
Section: Methodsmentioning
confidence: 99%